Cardiorenal Syndrome Mechanisms, Risk and Treatment - Berbari, Adel E.; Mancia, Giuseppe; SpringerLink (Online service) (Milano : Springer Milan, 2010)
Accelerated cardiovascular disease is a frequent complication of chronic kidney disease. Individuals with evidence of renal functional impairment are more likely to die of cardiovascular events than to progress to end stage renal disease. This relationship, which has been termed the cardiorenal syndrome, exists whether impairment of renal function is a consequence of primary renal parenchymal or primary heart disease. The mechanisms underlying the cardiorenal syndrome result from a complex interaction of traditional and uremia related cardiovascular risk factors. Prevention and management of cardiovascular disease include aggressive control of traditional risk factors as well novel approach to prevent or reverse uremia related processes. Chronic kidney disease with a worldwide prevalence of 10% in the general population is emerging as a major public health priority. Renal dysfunction is associated with a high risk for cardiovascular complications. The relationship between renal insufficiency and cardiovascular disease, termed the cardiorenal syndrome exists whether impairment of renal function is a consequence of primary renal parenchymal disease or primary heart disease. This book provides a comprehensive update analysis of our current understanding of the cardiorenal syndrome, including epidemiology, pathophysiologic mechanisms, and therapeutic approaches.
Chronic Kidney Disease and Cardiovascular Disease Interrelationships -- Links between Chronic Kidney Disease and Cardiovascular Disease: A Bidirectional Relationship -- Cardiorenal versus Renocardiac Syndrome -- Crosstalk between the Cardiovascular System and the Kidney -- Non-Pressure-Related Deleterious Effects of Excessive Dietary Sodium -- Regulation of Vascular and Renal Cells by Common Mediators in Health and Disease: Role of the Renin$1 (BAngiotensin System in the Pathophysiology of Hypertension and Cardiovascular Disease -- Chronic Kidney Disease as a Risk for Cardiovascular Disease -- Cardiorenal Continuum -- Definition and Classification of Stages of Chronic Kidney Disease: Screening for Chronic Kidney Disease -- Cardiovascular Disease Risk Factors in Chronic Kidney Disease: Traditional, Nontraditional, and Uremia-related Threats -- Increased Levels of Urinary Albumin: A Cardiovascular Risk Factor and a Target for Treatment -- Microalbuminuria and Kidney Disease: An Evidence-based Perspective -- Cardiometabolic Syndrome -- Diabetes Mellitus: Is the Presence of Nephropathy Important as a Cardiovascular Risk Factor for Cardioneral Syndrome? -- Spectrum of Cardiovascular Disease in Chronic Kidney Disease -- Cardiovascular Disease: Coronary Artery Disease and Coronary Artery Calcification -- Cardiomyopathy in Chronic Kidney Disease and in End-stage Renal Disease -- Pathophysiological Mechanisms and Prognostic Significance of Renal Functional Impairment in Cardiac Patients -- Stroke -- Mechanisms of Cardiovascular Complications -- Uremic Toxins -- Endothelial Dysfunction, Nitric Oxide Bioavailability, and Asymmetric Dimethyl Arginine -- Pathophysiologic Link between Atherosclerosis and Nephrosclerosis -- Aortic Stiffness, Kidney Disease, and Renal Transplantation -- Disturbed Calcium-Phosphorus Metabolism/Arterial Calcifications: Consequences on Cardiovascular Function and Clinical Outcome -- Role of Neurohormonal Activation in the Pathogenesis of Cardiovascular Complications in Chronic Kidney Disease -- Impaired Autonomic Blood Pressure and Blood Volume Control in Chronic Renal Failure -- Role of Novel Biomarkers in Chronic Kidney Disease: Urotensin II -- Role of Novel Biomarkers in Chronic Kidney Disease: Renalase -- Regression/Progression of Chronic Kidney Disease -- Diabetic Kidney Disease -- Nondiabetic Kidney Disease -- Therapeutic Modalities -- Approaches in the Management of Patients with Chronic Kidney Disease and Cardiovascular Disease -- Trends in the Management of Cardiac Patients with Renal Functional Impairment.s
Keywords: Medicine; Cardiology; Nephrology; Medicine & Public Health; Cardiology; Nephrology